The Problem of Nationalism in the Early Reformation - Scott, Tom (Renaissance and Reformation / Renaissance et Réforme, 2017)
Historians frequently dismiss any use of the term nationalism in the pre-modern period as conceptually illegitimate. In the early Reformation in Germany, the welter of confusing and competing terms to describe Luther’s audience—“nation,” “tongue,” “fatherland,” patria—appears to confirm that scepticism. At a regional level, however, where the descriptor Land lacks a precise English equivalent, a consciousness of local identity with undeniable “nationalist” connotations can be discerned, especially in the South-West borderlands with francophone areas. Yet this self-perception sits uneasily with comparable manifestations in Switzerland, where identity was not shaped agonistically over against “foreigners,” but was instead deployed by Zwingli and Bullinger to affirm a heroic past epitomized by valiant defence of true religion.